“Like you, I want to feel excitement and hope about our city”: ‘Christchurch the city’ in campaign material of the 2013 Christchurch City Council election - Carlton, Sally (Journal of Architecture and Urbanism, 2014)
The Christchurch City Council election of 2013 provides a compelling case study through which to consider the interaction between politics and city space. On the one hand, through the careful placement of campaign posters, politics encroached on the physical terrain of the city. On the other hand, candidates included in their campaign material multitudinous references to ‘Christchurch the city’, demonstrating the extent to which the physical environment of the post-disaster city had become central to local politics.